The West Pediment of the Parthenon : Iconography and Iconology - Mitsios, Ioannis (Classical Studies E-Books Online, Collection 2025, 2025)
This book offers a holistic study of the sculptures (and attributed fragments) of the west pediment of the Parthenon. For the very first time, the sculptures are examined in close relation to the drawings of the west pediment, as well as the iconography, myths, cults and topography of the Acropolis of Athens. The monograph offers nine new identifications, out of the fourteen heroic figures depicted on the west pediment of the Parthenon.